Association of AIRE Polymorphism and the Susceptibility to Multiple Sclerosis in Iranian Population - Sadeghian-Rizi, Tahereh (Avicenna J Med Biotechnol, 2018)
BACKGROUND: Multiple Sclerosis (MS) is the most common cause of neurologic disability in young adults. Recently, the AIRE gene was identified as a genetic risk factor for several autoimmune diseases in genome wide association studies. The aim of this study was to further investigate the possible role of the AIRE gene in susceptibility to MS in Iranian population. METHODS: A total of 112 MS patients and 94 ethnically matched controls were included in the study. The Single-Nucleotide Polymorphism (SNP) (rs1800520, C>G) with a global MAF=0.2282/1143 was selected and genotyped using HRM real-time PCR method. RESULTS: Results showed that AIRE SNP rs1800520 was significantly less common in the MS patients than in healthy controls (17.8 vs. 28.7%, pc=0.032, OR=0.54,95% CI 0.279, 1.042). Also, the frequency of allele G was significantly higher among the control group than in the case group (37.77 vs. 25%, pc=0.014). Interestingly, mRNA transcribed on the rs1800520 SNP showed decreased free energy than the wild type suggesting that its increased stability may be responsible for the different activities of the polymorphic AIRE molecule. CONCLUSIONS: This is the first study investigating the relationship between AIRE gene and the susceptibility to MS. These results indicated that the rs1800520 SNP is not a susceptibility gene variant for the development of MS in Iranian population.